Subject matter effects and the Community of Inquiry (CoI) framework: An exploratory study - Arbaugh, J.B.; Bangert, Arthur; Cleveland-Innes, Martha (The Internet and higher education, 2010)
This paper integrates the emerging literatures of empirical research on the Community of Inquiry (CoI) framework and disciplinary effects in online teaching and learning by examining the disciplinary differences in perceptions of social, teaching, and cognitive presence of over 1500 students in seven disciplines at two U.S. institutions. Our results found significant disciplinary differences, particularly regarding cognitive presence, in soft, applied disciplines relative to other disciplines. These initial results suggest the possibility that the CoI framework may be more applicable to applied disciplines than pure disciplines. Our findings suggest interesting opportunities for future researchers to consider how the individual elements of the CoI framework may influence and be influenced by academic disciplines and how the framework may need to be refined or modified to explain effective course conduct in pure disciplines.